From Leadership to Learning: Examining the Managerial Influence of School Principals on Teacher Effectiveness - Thaha, Hijaz; Pirol, Abdul; Guntur, Muhammad (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2025)
This study investigates the influence of school principals’ managerial competence on teacher instructional effectiveness in a religious-based secondary school (madrasah) in Indonesia. Managerial competence is conceptualized across three core dimensions: conceptual skills (strategic planning), human skills (interpersonal relations and motivation), and technical skills (administrative and instructional support). Employing a quantitative ex post facto design, data were collected from 16 teachers using structured questionnaires, non-intrusive observations, and document analysis. Linear regression analysis revealed a significant and positive relationship between principals’ managerial competence and teacher effectiveness (R² = 0.457, p = 0.002), with both variables rated in the